Effect of Turf Roof Slabs on Indoor Thermal Performance in Tropical Climates: A Life Cycle Cost Approach. (7th November 2013) - Halwatura, R. U.
Abstract : Urbanization related to population growth is one of the burning issues that the world is facing today. Parallel to this, there is visible evidence of a possible energy crisis in the near future. Thus, scientists have paid attention to sustainable development methods, and in the field of building construction also, several innovations have been proposed. For example, green roof concept is one of such which is considered a viable method mainly to reduce urban heat island effect, to regain lost land spaces in cities, and to increase aesthetics in cities. The present study was aimed at investigating the impact of green roofs on indoor temperature of buildings, the effect of different types of roofs on the air conditioning loads, and the life cycle cost of buildings with different types of roofing. The study was conducted in several phases: initial small-scale models to determine the heat flow characteristics of roof top soil layers with different thicknesses, a large-scale model applying the findings of the small-scale models to determine temperature fluctuations within a building with other common roofing systems, a computer simulation to investigate air conditioning loads in a typical building with cement fiber sheets and green roof slabs, a comparative analysis of the effect of traditional type roofs and green roofs on the air conditioning loads, and finally an analysis to predict the influence of traditional type roofs and green roofs on life cycle cost of the buildings. The main findings of the study were that green roofs are able to reduce the indoor temperature of buildings and are able to achieve better heat transfer through the roof, and, thus a lower cooling load is necessary for air conditioning and has the possibility of reducing life cycle cost of a building.